Nilai-Nilai Pendidikan Islam Pranatal Dalam Buku Profil Orang Betawi Karya Ridwan Saidi - Dicky Setiady (Departement of Mathematics Education, 2023)
This research aims to find out the process of internalizing prenatal Islamic education values in Betawi tradition, analyze the values contained therein, and identify the factors that hinder and support it. The research was conducted using a qualitative method of document analysis from the book